Planning a Protection Coordination System Against Over Current Relays and Ground Fault Relays Using the NN Method - Siti Zaibah; Anggara Trisna Nugraha; Fortunaviaza Habib Ainudin (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
PT PAMA PERSADA is one of the power plants located in Kalimantan, Barunang which has 2 feeders. In one of the feeders, protection coordination often occurs. These disturbances can hamper the performance of the company PT PAMA PERSADA. This turned out to be a disturbance in the coordination of protection types of overcurrent relays and ground fault relays. Where in the end it takes an evaluation analysis of the relay setting coordination using the Electrical Transient Analysis Program (ETAP) 19.0.1 software on the electrical system. The disturbance that occurs is in feeder 2 which is divided into KM30 and Parilahung substations. This disturbance occurs because the relay coordination trips work simultaneously. From the results of the ETAP simulation, the power value is 4.164 KW, the reactive power is 780.3 KVAR, the apparent power is 4.237 KVA, and the cos phi value used is 0.9. Meanwhile, the protection coordination setting meets the IEEE 60255 standard with a grading time of 0.2 – 0.6 second. After being successfully simulated with the Electrical Transient Analysis Program (ETAP) 19.0.1 software, it was continued with the Matlab software which was used as an optimization of the relay settings and the use of the working effect of the NN (Neural Network) method. In accordance with the MSE (Main Square Error) value it reached 0.33452.